RESPON VARIETAS TEBU UNGGUL BARU TERHADAP PEMBERIAN NANO SILIKA DAN CEKAMAN KEKERINGAN - Vega kartika sari; Kacung Haryono; Basuki Basuki (Jurnal Penelitian Pertanian Terapan, 2021)
The development pattern of sugarcane on the island of Java has shifted to dry land because rice fields are prioritized for other food crops. Dryland generally has low to moderate fertility rates and water availability is a limiting factor. Silicate (Si) is a beneficial nutrient for sugarcane and is absorbed in greater quantities than other nutrients. Si also can avoid damage to plants against abiotic stress such as drought. This study aims to test several new high-yielding sugarcane varieties under drought conditions and their responses to Si fertilization. The design used was three-factor RAK, namely the concentration of nano-silica fertilizer (0%; 30%; 45%), watering intensity (regular watering; no watering from 45 DAS), and new high yielding sugarcane varieties (BL; NX 01; NX 02; NX 03; VMC 86-550). The observation variables included stover fresh weight, root fresh weight, root length, and stover dry weight. The data obtained were analyzed by ANOVA at a 95% confidence level. If it is significantly different, continue with the 5% LSD test. Based on the results of this study, it was shown that the new superior sugarcane variety, namely VMC 86-550, was drought tolerant, indicated by the best average growth in almost all observed parameters. The concentration of nano-silica fertilizer 45% for 2 times the application showed the best growth of sugarcane. The treatment interaction between drought and variety had a significant effect on the wet weight of stover and root length of sugarcane. Treatment of nano-silica had a significant effect on the dry weight of sugarcane stover.